Alzheimer’s Disease: Drug Discovery 2020
DOI: 10.36255/exonpublications.alzheimersdisease.2020.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid ß-Targeted Inhibitory Peptides for Alzheimer’s Disease: Current State and Future Perspectives

Abstract: Alzheimer' s disease is the most common irreversible neurodegenerative disorder. To date, there is no cure for Alzheimer' s disease. While multiple pathological mechanisms have been proposed for the onset and progression of Alzheimer' s disease, the hypothesis that attracted much attention is the amyloid hypothesis. The senile plaques that accumulate in the brain of Alzheimer' s disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…-are too weak to go all the down the bench-to-bedside route [36,37], (ii) the timing of therapeutic intervention-which should be very early along the natural history of the disease-(iii) the phenotypic variability of AD [38]-that deeply affects and diversifies the responsiveness to treatments-and (iv) the complexity of disease pathogenesis suggesting that more than one target should be locked by therapeutic strategies to be successful in tackling the illness [7,39,40]. Overall these observations suggest that the optimal therapeutic strategy against AD should engage multiple allied molecular mechanisms, demonstrating efficacy not only in interfering with the well-known players in AD pathogenesis-i.e., Aβ, tau, neuroinflammation and others-but also in hindering their neurotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-are too weak to go all the down the bench-to-bedside route [36,37], (ii) the timing of therapeutic intervention-which should be very early along the natural history of the disease-(iii) the phenotypic variability of AD [38]-that deeply affects and diversifies the responsiveness to treatments-and (iv) the complexity of disease pathogenesis suggesting that more than one target should be locked by therapeutic strategies to be successful in tackling the illness [7,39,40]. Overall these observations suggest that the optimal therapeutic strategy against AD should engage multiple allied molecular mechanisms, demonstrating efficacy not only in interfering with the well-known players in AD pathogenesis-i.e., Aβ, tau, neuroinflammation and others-but also in hindering their neurotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The approach based on D-peptides is very promising because of their characteristics including high resistance to protease digestion, stability, and bioavailability [37], which make them optimal molecular prototypes for the development of drugs for the treatment of neurological disorders [55]. Actually, Aβ1-6 A2V (D) may be included in the class of 'amyloid β-targeted peptide inhibitors', which have special properties, including high selectivity, low accumulation in tissues, low side-effects and toxicity, and different chemical and biological synthesis routes when compared with other compounds used for therapeutic purposes [36,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Safura Jokar et al. have demonstrated that the KLVFFA peptide segment which is considered as the short active sequence of the β‐Amyloid peptide related to Alzheimer's disease (AD), [28–31] could self‐assemble, as the residues have a central hydrophobic core (CHC), that can act as the critical nucleation site [32] …”
Section: Introductionmentioning
confidence: 99%
“…[27] Safura Jokar et al have demonstrated that the KLVFFA peptide segment which is considered as the short active sequence of the β-Amyloid peptide related to Alzheimer's disease (AD), [28][29][30][31] could self-assemble, as the residues have a central hydrophobic core (CHC), that can act as the critical nucleation site. [32] The above-mentioned aggregation in the majority are reported mostly in organic solvent, where water is used as cosolvent in a few cases. However, it would not be determined whether the driving factor is the aromatic moiety (Fmoc) associated at the N-terminal, or the conjugate effect of both the N-terminal protecting group along with the aromatic residue in the hydrophobic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Ab42 contains two hydrophobic regions, Ala30-Val36 (at the C terminal) and Leu17-Ala21, referred to as the Central Hydrophobic Core (CHC) [28,29]. Ab-based peptide inhibitors are based on the structure of the C-terminal fragments (CTF) and the CHC sequences of the Ab peptide [30]. They bind to the Ab peptide at specific sites and prevent its assembly into amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%